Screened alpha decay in Dense Astrophysical Plasmas and Superstrong Magnetic Fields - Liolios, Th. E. (HNPS Advances in Nuclear Physics, 2020)
This paper shows that ultrastrong magnetic fields (such as those of magnetars) and dense astrophysical plasmas can reduce the half life of alpha decaying nuclei by many orders of magnitude. In such environments the conventional Geiger-Nuttall law is modifed so that all relevant half lives are shifted to dramatically lower values.